Neuroprotection of nalmefene for postoperative patients with spontaneous intracerebral hemorrhage. (2nd December 2015) - Zheng, Jun; Li, Hao; Guo, Rui; Chen, Ruiqi; Lin, Sen; Liu, Ming; You, Chao
Abstract : Background: Endogenous opiates play an important role in the secondary injury of brain tissue after central nervous system injury. It was confirmed that nalmefene, an opiates receptor antagonist, has neuroprotective efficacy in animal models. However, evidence of nalmefene treatment for surgical patients with spontaneous intracerebral hemorrhage is insufficient. Methods: Outcomes of patients treated with nalmefene were retrospectively compared with that of patients without any anti-opiate treatment. The primary outcome was functional outcome at 6 months post ictus, which was assessed using modified Rankin Scales (mRSs). Secondary outcomes included mortality in 30 d post ictus, state of consciousness evaluated using Glasgow Coma Scale (GCS) at 1, 3, 7 d post operation and complications. Results: Of 79 patients in the nalmefene treatment group, 22 (27.85%) had a favorable functional outcome at 6 months, while in the control group, 12 of 72 (16.67%) had the same result ( p = 0.273). A significantly better outcome was observed in the treatment group during only one subgroup analyses which was GCS between 3 and 8 (32.26% vs. 6.45%, p = 0.006). Conclusions: Nalmefene treatment was safe for patients with spontaneous intracerebral hemorrhage but could not improve the outcome of either short-term consciousness or long-term functional outcome.